PREPARATION AND CHARACTERIZATION OF NANOCRYSTALS FOR SOLUBILITY AND DISSOLUTION RATE ENHANCEMENT OF PALIPERIDONE USING DIFFERENT HYDROPHILIC CARRIERS: IN VITRO-IN VIVO STUDY - Rajkumar, Moon; Surendra, Gattani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to increase the solubility and dissolution rate of paliperidone (PAL) by preparing its nanocrystals using different hydrophilic carriers by antisolvent precipitation technique. Methods: The nanoparticles (NP) were characterized for aqueous solubility, drug content, Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction, scanning electron microscopy, particle size, and in vitro-in vivo analysis. Results: The results showed improved solubility and dissolution rate of NPs when compared to pure drug and physical mixture (PM). Solubility data showed a linear graph giving an indication that there is a gradual increase in the solubility profile of the drug with an increase in concentration of the carriers. At highest concentration, the solubility of NPs with Plasdone S630, Povidone K-25, and PVP K-30 found to be increased by 12 folds, 9 folds and 6 folds, respectively, as compared to pure drug. The release profile of NPs with Plasdone S630 in terms of dissolution efficiency at 60 min (DE60), initial dissolution rate (IDR), amount release in 15 min (Q15 min), and time for 75% release (t75%) shows better results when compared to pure drug, PM, and also NPs with povidone 25 and povidone 30. In vivo study reveals that optimized NPs elicited significant induction of cataleptic behavior which is the indication of antipsychotic agent(s) effect. Conclusion: The process antisolvent precipitation under constant stirring may be a promising method to produce stable PAL NPs with markedly enhanced solubility and dissolution rate due to nanonization with the increased surface area, improved wettability, and reduced diffusion pathway.